Nutritional status of urban adolescents: individual, household and neighborhood factors based on data from The BH Health Study - Stephanie Bispo; Maria Isabel Toulson Davisson Correia; Fernando Augusto Proietti; César Coelho Xavier; Waleska Teixeira Caiaffa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract The increasing prevalence of overweight in young people suggests that adolescent nutritional status is influenced by environmental factors. Using hierarchical modelling, this study aimed to analyse the association between individual, household and neighborhood factors and adolescent nutritional status and well-being. The study used data from a population-based household survey conducted in Belo Horizonte, the capital of the State of Minas Gerais, Brazil, between 2008 and 2009. Data was obtained from an adult and adolescent in each household using a confidential questionnaire and anthropometric measurements. Adolescent nutritional status was evaluated using multinomial regression analysis considering distal and proximal influences. The prevalence of overweight and thinness among the sample of 1,030 adolescents was 21.9% and 4.6%, respectively. Although variables from all blocks remained in the final model, head of household education level, family habits and family nutritional status were shown to strongly influence adolescent nutritional status. New approaches to public health are needed which focus on raising awareness and promoting health education targeting teenagers and their social context.